Do You Need a Job to Find a Job? - Deborah A. Cobb-Clark; Paul Frijters; Guyonne Kalb (Institute for the Study of Labor (IZA), 2004)
This paper investigates whether job offers arrive more frequently for those in employment than for those in unemployment. To this end, we take advantage of a unique Australian data set which contains information on both accepted and rejected job offers. Our estimation strategy takes account of the selectivity associated with the initial employment state and we allow for individual heterogeneity in the probability of obtaining jobs. Our results reveal that, across the wage range, individuals are about equally likely to obtain a job offer in employment as in unemployment. This implies that encouraging unemployed (rather than employed) search through the provision of unemployment benefits does not improve the speed of a job match.
Keywords: J64; C14; C41; 330; job-offer arrival rates; reservation wages; wage-offer distribution; directed search; Arbeitsnachfrage; Arbeitsuche; Erwerbsverlauf; Anspruchslohn; Schätzung; Australien